Differences between the real and the desired worlds in the results of clinical trials - Regina El Dib; Eliane Chaves Jorge; Amélia Kamegasawa; Solange Ramires Daher; Regina Stella Spagnuolo; Marise Pereira da Silva; Gabriel Pereira Braga; Enilze Volpato; Norma Sueli Pinheiro Módolo; Marluci Betini; Adriana do Valle; Ione Corrêa; et al. (Clinics, 2015)
OBJECTIVE: We refer to the effectiveness (known as pragmatic or real world) and efficacy (known as explanatory or desired or ideal world) of interventions. However, these terms seem to be randomly chosen by investigators who design clinical trials and do not always reflect the true purpose of the study. A pragmatic-explanatory continuum indicator summary tool was thus developed with the aim of identifying the characteristics of clinical trials that distinguish between effectiveness and efficacy issues. We verified whether clinical trials used the criteria proposed by the indicator summary tool, and we categorized these clinical trials according to a new classification. METHOD: A systematic survey of randomized clinical trials was performed. We added a score ranging from 0 (more efficacious) to 10 (more effective) to each domain of the indicator summary tool and proposed the following classifications: high efficacy (<25), moderate efficacy (25-50), moderate effectiveness (51-75), and high effectiveness (<75). RESULTS: A total of 844 randomized trials were analyzed. No analyzed trials used the criteria proposed by the indicator summary tool. Approximately 44% of the trials were classified as having moderate effectiveness, and 43.82% were classified as having moderate efficacy. CONCLUSIONS: Most clinical trials used the term “efficacy” to illustrate the application of results in clinical practice, but the majority of those were classified as having moderate effectiveness according to our proposed score. The classification based on the 0-100 score is still highly subjective and can be easily misunderstood in all domains based on each investigator’s own experiences and knowledge.